Analysis on the Noise for the Different Gearboxes of the Heavy Truck - Zhixian Zhong; Zhansi Jiang; Yuhong Long; Xin Zhan (Shock and Vibration)
In order to locate the excessive noise caused by gearbox noise when a heavy vehicle is accelerating, the noise and vibration on the key parts of the gearbox were tested and analyzed, and the peak noise frequency of radiating from the subbox of gearbox was found, which is the same as the peak frequency of pass-by noise. Aiming at the larger gear noise of the gearbox subbox, the experiments of pass-by noise by the two ways of the different speed-ratio gearbox, and the transformation of vice-box with helical gear, the pass-by noise was reduced by 5.6 and 3.9 dB(A), and it was made to reach the less GB limit-value. Meanwhile, the effect of the different-ratio gearbox on the vehicle noise was analyzed. So, the methods provide a practical basis for the vehicle noise and the fault diagnosis of gearbox.